UJI FORMULASI PUPUK HAYATI DAN PUPUK NPK PADA PERTUMBUHAN BIBIT KELAPA SAWIT (Elaies guineensis Jacq.) DI PEMBIBITAN UTAMA - Sudarno Sudarno; Adiwirman Adiwirman; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Palm oil plantations are plantation crops for Indonesia and plays an important role as a mainstay commodity for export or commodities that can increase farmers' income. To produce a good seedlings and the required quality of intensive management during the nursery stage one was fertilization. Fertilization is made to enhance the growth of oil palm seedlings, one of them with biological fertilizer combined with inorganic fertilizer. This study aims to determine the effect of the interaction of multiple doses of biological fertilizers and NPK fertilizers by administering several different doses on the growth of oil palm seedlings and to get the best interactions in the main nursery. This study was conducted at experimental field of Faculty of Agriculture, University of Riau with Inceptisol soil types. The research was conducted from January 2016 to April 2016. This study was conducted experiments using a completely randomized design (CRD) factorial consisting of two factors: Factor I: bacillusyang biological fertilizer consists of four levels IE K0: Without giving a biological fertilizer bacillus, K1: fertilizer biological active ingredient bacillus sp 10 ml / plant, K2: fertilizer biological active ingredient bacillus sp 20 ml / plant and K3: fertilizer biological active ingredient bacillus sp 30 ml / plant. Factor II: NPK fertilizer, which consists of four levels IE P0: Without giving NPK, P1: Delivery of NPK 5g / plants, P2: Delivery of NPK 10 g / plant and P3: Delivery of NPK 15 g / plant. The parameter those observed were the seedlings height (cm), stump diameter (cm), number of leaves (leaf), plant fresh weight (g), seedling dry weight (g), the volume of the roots of plants (ml) and the shoot to root ratio .The results showed that doses of biofertilizers 30 ml / plant and without NPK fertilizer showed the highest results, namely, plant height, diameter of the stump, leaf number, fresh weight of plants, plant dry weight, root volume and the ratio of canopy roots and several doses of NPK does not give effect to all the parameters of observation.